Keseimbangan Pasar Barang dalam Perspektif Ekonomi Islam dan Konvensional: Analisis Kurva IS - Azzahra Meytriana; Maulida Hasyima; Suci Hayati (Teewan Journal Solutions, 2025)
The goods market is a key component in macroeconomic analysis, as it determines the equilibrium between output and national income, in conventional economics, the equilibrium of the goods market is analyzed using the IS Investment-Saving curve, which shows a negative relationship between interest rates and national income. However, this approach is not aligned witah Islamic economic principles, as it relies on interest (riba), which is prohibited under Sharia law. Instead, Islamic economics employs a profit-sharing mechanism through instruments such as mudharabah to determine investment returns. This approach also emphasizes the importance of moral values, ethics, and social justice as integral parts of a more civilized economic system. Within the Islamic framework, the IS curve still reflects the relationship between investment and savings, but without involving elements of riba. It is instead grounded in principles of justice, transparency, and public welfare.